“WINS” untuk Pengelolaan Kawasan Lindung Berdasarkan Sistem Agroforestri Aren (Arenga pinnata) di Zona Rehabilitasi Taman Nasional Meru Betiri - Rahmatan Rahmatan; Yulia Raudhatul Balaqis Zahro; Safira Azizah (Jurnal Ilmu Pertanian Indonesia, 2021)
WINS" (Win-Win Strategy) in the management of protected areas is the strategy that benefit both parties. Agroforestry with forest trees accompanied by agricultural crops may benefits the community if it is implemented in line with the management of Meru Betiri National Park (TNMB) policies. The agroforestry plants proposed in this study were aren (Arenga pinnata), java chili (Piper retrofractum), and porang (Amorphophallus muelleri). This study recommends four strategies for better agroforestry practice in TNMB, i.e.,g. 1) strategy I, increasing public awareness of the urgency of the preservation of national park areas; 2) strategy II, formulating policies to support agroforestry as a strategic management effort; 3) strategy III, education and counseling, as a strengthening of the role of extension workers; and 4) strategy IV, facilitating access to relevant data across all participating institutions and is supported in a multidisciplinary manner. This model may be used as a reference for agroforestry models in conservation areas, especially in TNMB, which will optimize the development of native plants in an area. Keywords: agroforestry, Arenga pinnata, Meru Betiri National Park, SWOT analysis, win-win strategy